Fully automated magnetically controlled capsule endoscopy for examination of the stomach and small bowel: a prospective, feasibility, two-centre study. (November 2021) - Xiao, Yu-Feng; Wu, Zhi-Xuan; He, Song; Zhou, Yuan-Yuan; Zhao, Yong-Bing; He, Jia-Lin; Peng, Xue; Yang, Zhao-Xia; Lv, Qing-Jian; Yang, Huan; Bai, Jian-Ying; Fan, Chao-Qiang; et al.
Summary: Background: The use of magnetically controlled capsules for gastroscopy is in the early stages of clinical adoption. We aimed to evaluate the safety and efficacy of a fully automated magnetically controlled capsule endoscopy (FAMCE) system in clinical practice for gastroscopy and small bowel examination. Methods: We did a prospective, comparative study to evaluate the safety and efficacy of FAMCE. Patients from two hospitals in Chongqing, China were consecutively enrolled. Eligible participants were aged 18–80 years with suspected gastric pathology and no previous surgery. Participants underwent FAMCE for screening of gastric lesions, then conventional transoral gastroscopy 2 h later, and stomach examination results were compared. The primary outcome was the rate of complete detection of gastric anatomy landmarks (cardia, fundus, body, angulus, antrum, and pylorus) by FAMCE. Secondary outcomes were the time required for gastric completion by FAMCE, the rate of detection of gastric lesions by FAMCE compared with conventional transoral gastroscopy, and the rate of complete small bowel examination. Adverse events were also evaluated. The study was registered in the Chinese Clinical Trial Registry, ChiCTR2000040507. Findings: Between May 12 and Aug 17, 2020, 114 patients (mean age 44·0 years [IQR 34·0–55·0]; 63 [55%] female) were enrolled. The rate of complete detection of gastric anatomical structures by FAMCE was 100% (95% CI 99·3–100·0). The concordance between FAMCE and conventional transoral gastroscopy was 99·61% (99·45–99·78). The mean completion time of a gastroscopy with FAMCE was 19·17 min (SD 1·43; median 19·00, IQR 19·00–20·00), compared with 5·21 min (2·00; 5·18, 3·68–6·45) for conventional transoral gastroscopy. In 114 enrolled patients, 214 lesions were detected by FAMCE and conventional transoral gastroscopy. Of those, 193 were detected by both modalities. FAMCE missed five pathologies (four cases of gastritis and one polyp), whereas conventional transoral gastroscopy missed 16 pathologies (12 cases of gastritis, one polyp, one fundal xanthoma, and two antral erosions). FAMCE was able to provide a complete small bowel examination for all 114 patients and detected intestinal lesions in 50 (44%) patients. During the study, two (2%) patients experienced adverse events. No serious adverse events were recorded, and there was no evidence of capsule retention. Interpretation: The performance of FAMCE is similar to conventional transoral gastroscopy in completion of gastric examination and lesion detection. Furthermore, it can provide a complete small bowel examination. Therefore, FAMCE could be effective method for examination of the gastrointestinal tract. Funding: Chinese National Key Research and Development Program.